2022
DOI: 10.1101/2022.01.27.477927
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A wheat kinase and immune receptor form the host-specificity barrier against the blast fungus

Abstract: Since emerging in Brazil in 1985, wheat blast has spread throughout South America and recently appeared in Bangladesh and Zambia. We show that two wheat resistance genes, Rwt3 and Rwt4, acting as host-specificity barriers against non-Triticum blast pathotypes encode a nucleotide-binding leucine-rich repeat immune receptor and a tandem kinase, respectively. Molecular isolation of these genes allowed us to develop assays that will ensure the inclusion of these two genes in the wheat cultivars to forestall the re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…These tandem kinase genes include Rpg1, Yr15, Sr60, Sr62, Pm24, WTK4, and Rwt4 (refs. [7][8][9][10][11][12][13] ). Other resistance genes offer some variation to this architecture with protein kinases fused to a steroidogenic acute regulatory protein-related lipid transfer domain (Yr36) 14 , a C2 domain and a multi-transmembrane region (Pm4) 15 , a major sperm protein (Snn3) 16 , an NLR (Tsn1, Rpg5, and Sm1) 17,18,19 , and a von Willebrand factor type A domain (Lr9) 20 .…”
Section: Mainmentioning
confidence: 99%
“…These tandem kinase genes include Rpg1, Yr15, Sr60, Sr62, Pm24, WTK4, and Rwt4 (refs. [7][8][9][10][11][12][13] ). Other resistance genes offer some variation to this architecture with protein kinases fused to a steroidogenic acute regulatory protein-related lipid transfer domain (Yr36) 14 , a C2 domain and a multi-transmembrane region (Pm4) 15 , a major sperm protein (Snn3) 16 , an NLR (Tsn1, Rpg5, and Sm1) 17,18,19 , and a von Willebrand factor type A domain (Lr9) 20 .…”
Section: Mainmentioning
confidence: 99%
“…Studies also reported host genes that recognize specific pathogen genes and provide resistance against WB. Rwt3 and Rwt4 are such non-host resistant genes in wheat that recognize pathogen genes PWT3 and PWT4, respectively, resulting in an incompatibility (resistant) reaction [31,32]. Similarly, a hypothesis involving such interaction was proposed for the origin of WB in Brazil, which was due to large-scale cultivation of a variety lacking Rwt3 that led to the susceptible reaction of majority wheat varieties to a mutated Lolium-like pathotype of M. oryzae, later known as MoT [33].…”
Section: Introductionmentioning
confidence: 99%
“…Sr43 contains a kinase domain fused to two domains of unknown function that might serve as decoys. Together, these two studies highlight the emerging role of unusual kinase fusion proteins in wheat disease resistance [13][14][15][16][17][18][44][45][46][47] , which will form the basis to utilize this protein class in breeding. (128 F2 plants), respectively.…”
mentioning
confidence: 99%
“…1d). Wheat tandem kinases (WTKs) have recently emerged as a new prominent player involved in disease resistance in Triticeae, the botanical tribe including wheat and barley [12][13][14][15][16][17][18] . The fusion of a WTK to another domain, however, is unique and highly unusual.…”
mentioning
confidence: 99%
See 1 more Smart Citation